Parity of Calving Influences the Likelihood of Calves Having Cryptosporidium spp. - Alīna Zolova; Dace Keidāne; Maksims Zolovs (Veterinary Medicine International)
The effect of colostrum on calves’ health status was intensively studied, while the role of transition milk was left underestimated. The common practice is to feed calves with an adequate amount of colostrum immediately after calving and soon after feeding calves are weaned from dams. In this research, calves were not weaned from dams for at least 2 weeks receiving both colostrum and transition milk on demand. Thus, we have recreated natural feeding conditions for calves’ development. We used a stratified sample method to test whether the size of the dairy cattle farms, breed, parity number, season of calving, and length of the dry period affect the likelihood of calves’ infection with Cryptosporidium spp. considering these factors influence both colostrum and transition milk quality. The main results showed that 26.1% of calves were positive for the presence of Cryptosporidium spp. oocysts. The presence of clinical signs of diarrhea was recorded in 15% of the positive animals. Regression analysis showed that multiparous cows decrease the chance of calves to have Cryptosporidium spp. by 82%–89%, while cows calved on small farms decrease the chance of calves to have Cryptosporidium spp. by 80%. We suggest that primiparous cows are spending inner resources primarily on their maturation, thereby leaving the prerequisites for the infection of their offspring, while intense farming just increases the chance of unprotected calves to obtain infections.